Current status of the lateral flow immunoassay for the detection of SARS-CoV-2 in nasopharyngeal swabs - Somborac Bačura, Anita (Array, 2021)
Early detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and diagnosis of coronavirus disease 2019 (COVID-19) are priorities during the pandemic. Symptomatic and suspected asymptomatic individuals should be tested for COVID-19 to confirm infection and to be excluded from social interactions. As molecular testing capacity is overloaded during the pandemic, rapid antigen tests, such as lateral flow immunoassays (LFIAs), can be a useful tool as they allow greater test availability and obtain results in a very short time. This short review aims to present the analytical properties of LFIAs in the detection of SARS-CoV-2 in nasopharyngeal swabs. Lateral flow immunoassay is a method that combines thin-layer chromatography and indirect immunochemical sandwich method and allows the detection of a specific SARS-CoV-2 antigen in nasopharyngeal swabs. Swab specimens should be adequately collected and tested as soon as possible. Users should pay attention to quality control and possible interferences. Antigen tests for SARS-CoV-2 show high sensitivity and specificity in cases with high viral loads, and should be used up to five days after the onset of the first symptoms of COVID-19. False positive results may be obtained when screening large populations with a low prevalence of COVID-19 infection, while false negative results may happen due to improper specimen collection or insufficient amount of antigen in the specimen. So as to achieve reliable results, a diagnostic accuracy study of a specific rapid antigen test should be performed.